2022
DOI: 10.1002/acm2.13566
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional deep neural network for automatic delineation of cervical cancer in planning computed tomography images

Abstract: Purpose Radiation therapy is an essential treatment modality for cervical cancer, while accurate and efficient segmentation methods are needed to improve the workflow. In this study, a three‐dimensional V‐net model is proposed to automatically segment clinical target volume (CTV) and organs at risk (OARs), and to provide prospective guidance for low lose area. Material and methods A total of 130 CT datasets were included. Ninety cases were randomly selected as the training data, with 10 cases used as the valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Collaborative research across multiple countries is crucial for advancing scientific knowledge and developing effective solutions to global challenges. However, our analysis of 77 original articles revealed that only a small proportion (18.18%) involved collaboration among authors from two [ 37 , 55 , 63 , 65 , 71 , 75 , 78 , 81 , 84 , 85 , 105 ] or three [ 70 , 91 , 92 ] different countries. This suggests that there is still a lack of international collaboration and data sharing in the field.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Collaborative research across multiple countries is crucial for advancing scientific knowledge and developing effective solutions to global challenges. However, our analysis of 77 original articles revealed that only a small proportion (18.18%) involved collaboration among authors from two [ 37 , 55 , 63 , 65 , 71 , 75 , 78 , 81 , 84 , 85 , 105 ] or three [ 70 , 91 , 92 ] different countries. This suggests that there is still a lack of international collaboration and data sharing in the field.…”
Section: Resultsmentioning
confidence: 89%
“…A limitation of the model-based approaches is potential biases in small datasets, such as studying gender-biased data [ 47 ]. Insufficient data to train the models was an issue in most of the studies in this review [ 13 , 39 , 44 , 45 , 47 , 65 , 90 , 105 , 106 , 107 ]. Lu et al, 2020 [ 66 ] adopted a strategy of transforming the image segmentation issue into a pixel-wise classification issue.…”
Section: Discussionmentioning
confidence: 99%
“…sCT, on the other hand, had a significant difference between bladder contour ASD on CBCT and sCT. The ASD was less than two times the ASD of deep‐learning segmentations compared to manual delineations of bladder in female pelvis 26–28 . This variation can be due to the performance of anatomical preservation of the deep‐learning network 16,29 .…”
Section: Discussionmentioning
confidence: 94%
“…The ASD was less than two times the ASD of deep-learning segmentations compared to manual delineations of bladder in female pelvis. [26][27][28] This variation can be due to the performance of anatomical preservation of the deep-learning network. 16,29 If the anatomical preservation is low, it could influence plan selection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the scope of auto-segmentation has been expanded to arterial intelligence (AI)-based contouring using deep learning algorithms (24)(25)(26)(27)(28)(29). Earlier work by Liu (30) demonstrated that the mean DSC values of deep learning-based methods were 0.924 for the bladder, 0.906 for the femoral head-L, 0.900 for the femoral head-R, 0.791 for the rectum, and 0.827 for the spinal cord.…”
Section: Discussionmentioning
confidence: 99%